Degradation of an Ethylene Carbonate/Diethyl Carbonate Mixture by Using Ionizing Radiation. Issue 19 (10th May 2017) - Wang, Furong; Varenne, Fanny; Ortiz, Daniel; Pinzio, Valentin; Mostafavi, Mehran; Le Caër, Sophie
Abstract: The reactivity of ethylene carbonate (EC) and of a EC/diethyl carbonate (DEC) mixture was studied under ionizing radiation to mimic the aging phenomena that occur in lithium‐ion batteries. Picosecond‐pulse radiolysis experiments showed that the attachment of the electron to the EC molecule is ultrafast ( k (e − EC +EC)=1.3×10 9 L mol −1 s −1 at 46 °C). This reaction rate is accelerated by a factor of 5.7 compared with the electron attachment to propylene carbonate, which implies that the presence of the methyl group significantly slows the reaction. In a 50:50 EC/DEC mixture, just after the electron pulse the electron is solvated by a mixture of EC and DEC molecules, but its fast decay is attributed exclusively to electron attachment to the EC molecule. Stable products detected after steady‐state irradiation were mainly H2, CH4, CO, and CO2 . The evolution of the radiolytic yields with the EC fraction shows that H2 and CH4 did not exhibit linear behavior, whereas CO and CO2 did. Indeed, H2 and CH4 mainly arise from the excited state of DEC, the formation of which is significantly affected by the evolution of the dielectric constant of the mixture and by the electron attachment to EC. CO formation is mainly due to the reactivity of the EC molecule, which is not affected in the mixture, as proven by pulse‐radiolysis experiments. Abstract : Mimicking battery aging : The aging of electrolytes in lithium‐ion batteries is studied by radiolysis that simulates accelerated aging. Ultrafast decay of the solvated electron in a mixture of ethylene carbonate (EC)/diethyl carbonate (DEC) is attributed to the electron attachment on the EC molecule exclusively, which leads to the formation of the EC radical anion.